Polyacrylamide-induced coagulation process removing suspended solids from palm oil mill effluent - Zinatizadeh, A.A.; Ibrahim, S.; Aghamohammadi, N.; Mohamed, A.R.; Zangeneh, H.; Mohammadi, P. (Taylor & Francis, 2017)
Palm oil mill effluent (POME) is a colloidal suspension with 2–4% suspended solids. About 50% of the suspended solids are cellulosic compounds, which are not degraded in the typical biological treatment systems. Chemical (polymer-induced coagulation) and physical (settling) pretreatment methods were examined to remove the suspended solids in this study. A novel physicochemical treatment with high water recovery and sludge compressibility including three cationic polyacrylamides (C-PAM; as coagulant) and three anionic polyacrylamides (A-PAM; as flocculant) with different molecular weights and charge densities was used. The coagulants used were biodegradable. The combination of a C-PAM (Chemfloc1515C) with medium molecular weight and charge density and an A-PAM (Chemfloc 430A) with high molecular weight and charge density at doses of 300 and 50 mg/dm3 showed the best total suspended solids (TSS) and chemical oxygen demand (COD) removal (96.4 and 70.9%, respectively). The optimal condition was found at pH 5, rapid mixing at 150 rpm for 1 min, and slow mixing at 40 rpm for 30 s. As a conclusion, the physiochemical pretreatment using biodegradable coagulants was a promising alternative to effectively separate TSS (96.4%) with high water recovery (76%).